The lived experiences of nurses caring for burn victims at a burns unit of a public sector academic hospital in Johannesburg - Kamalizeni, Dorothy (My University, 2016)
This study was intended to investigate the lived experiences of nurses caring for patients with burn injuries. A qualitative, phenomenological descriptive design based on Husserl`s (1962) philosophy, was used to achieve the study`s objectives. Registered nurse participants (n=13) were recruited from the adult and children`s burns units of a public sector academic hospital in Johannesburg. Data was collected using in-depth interviews with the participants, which provided them with an opportunity to express their experiences and opinions regarding caring for patients with burn injuries. The collected data was analysed using a descriptive methodology utilising Colaizzi`s (1978) data analysis approach. There was a general expression amongst the participants that caring for patients with burn injuries induced both physical and emotional discomfort, however good patient outcome was a source of gratification. The source of stress included labour intensity, unsightly nature of wounds and limitations in the provision for burns care with emphasis on shortage of nursing staff and lack of organisational support. There were apparently strong expressions that on-job training without recognisable certification made the nurses and others doubt their capabilities in burns nursing practice. The desire was for speciality training relating to burns care, with accompanying recognisable certification. Despite the prevailing challenges, the participants exhibited caring behaviour characterised by commitment to duty, passion for the job and compassion for the patients, which all enhanced professional boundaries and accountability. The findings of the study further reflected that the participants acknowledged management and other sources of vi external support. However, there was evidence that participants engaged in establishing their own mechanisms of coping with the prevailing challenges related to their job through self-motivation, resilience, team work and team support. It was apparent the participants demonstrated self-determination, perseverance and suppressed their stressful feelings to continue with the nature of their work. The findings of this study suggest that a supportive work environment coupled with competency and empowerment among the nurses are critical for the wellbeing of the patients and nursing staff in passing swiftly through the burns caring process. As the field of burns care is just developing, especially in the Low and Middle Income Settings, a lot of research is needed to determine the clinical, educational and management gaps in burns care with focus on nursing perspectives. Replica studies can therefore be conducted in other burns care settings to compliment the findings of the current study.
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2015.